Detecção e epidemiologia de doenças vesiculares no Brasil - Poliana de Oliveira Figueiredo (2015)
In Brazil, cattle raising is a growing activity and the country holds the world's premier position in the production and exportation of bovine derivatives. Many vesicular diseases caused by viruses can affect livestock production, especially bovine viral diarrhea, vesicular stomatitis and bovine herpes, which present very similar symptoms and with foot and mouth disease, which is highly contagious and causes great economic and social losses. Despite of the wide detrimental effects of these viruses on Brazilian livestock, data about circulation of Bovine viral diarrhea virus (BVDV), Vesicular stomatitis virus (VSV), Bovine herpesvirus 1(BoHV-1), Bovine herpesvirus 2 (BoHV-2) e Bovine herpesvirus 5 (BoHV-5) are still scarce and the few available data are mainly retrospective serologic studies. Thus, the objective of this study was to perform a molecular epidemiological study for detection and characterization of the most frequent genotypes and subgenotypes in the states of Minas Gerais, Bahia, Espirito Santo and Goiás in the years of 2012 to 2014. Screening was carried out by the use of a qPCR molecular diagnostics platform, followed by conventional PCR and sequencing for characterization. It was detected 32% (77/240) of positivity for BVDV, being the most frequent detection in Minas Gerais and the totality of characterized samples grouped in BVDV-1a subgenotype. For VSV, 13% (18/142) of the samples were positive and for BoHV- 1/5, 8%, and in both cases the majority of these animals were from Espírito Santo state. There were no positive samples diagnosed for BoHV-2. Cases of co-infections with BVDV and VSV were found in four animals, two animals were positive for BVDV and BoHV-5 and in three samples both VSV and BoHV1/5 were detected.